Assessment of agricultural practices by Ethiopian women farmers: existence of gender disparities in access to mycotoxins training - Cervini, Carla; Abegaz, Beimnet; Mohammed, Abdi; Elias, Raisa; Medina, Angel; Gebre, Kiros; Verheecke-Vaessen, Carol (Wageningen Academic Publishers, 2023)
Ethiopia is one of the countries with the lowest gender-equality performance in sub-Saharan Africa being ranked 121/134 in terms of the magnitude and scope of gender disparities by the United Nations Women’s Organisation. Within the farming communities, women represent 70% of the labour force, but they are neglected from accessing training events run by Ethiopian Universities (e.g. Haramaya University). A survey to assess the existence of gender disparities among Ethiopian women farmers with respect to agricultural labour and mycotoxins knowledge was conducted on three hundred and forty-nine women from the Oromia and Amhara regions. A higher illiteracy rate was found in women compared to men from both Oromia and Amhara regions. Women played a key role in agricultural activities while having limited access to modern technologies compared to their male counterparts. Women were mainly responsible for sorting spoiled crops. Especially in Amhara, these were intended for home consumption, representing a serious health risk for local people. Overall, women from Amhara were more aware than women from Oromia about what mycotoxins are (e.g. aflatoxins), their impact and risk of occurrence in crops. Women in Amhara were also more intended to act towards mycotoxins in the future compared to women from Oromia. Only 0.24% of women have previously attended a training on mycotoxins. The radio seemed to be the most efficient way to deliver training to Ethiopian women farmers from these regions. Mycotoxins trainings were the second option of choice by all women surveyed. Such findings clearly stated the existence of gender inequality in the two Ethiopian regions considered. Empower women’s knowledge about mycotoxins will not only benefit agricultural income and the national economy, but it will also provide women the recognition they equally deserve alongside their male counterparts in future agricultural training programs and interventions.
Keywords: Aspergillus flavus; aflatoxin B1; intervention strategies; food safety